2007
DOI: 10.1002/hep.21778
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the interleukin-6 C174G gene polymorphism on treatment of acute and chronic hepatitis C in human immunodeficiency virus coinfected patients

Abstract: Hepatitis C virus (HCV)/human immunodeficirency virus (HIV) coinfection poses a difficult therapeutic problem.Response to HCV-specific therapy is variable but might be influenced by host genetic factors, including polymorphisms of cytokine genes. Here, we studied whether interleukin-6 (IL-6) C174G gene polymorphism affects the response to antiviral treatment in HCV-infected HIV-positive subjects. We determined IL-6 genotypes in HIVpositive patients with acute (n ‫؍‬ 52) and chronic (n ‫؍‬ 60) hepatitis C treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 29 publications
4
33
3
Order By: Relevance
“…These findings were in agreement with the results of Nattermann et al [10], who reported that a higher level of IL-6 is significantly associated with SVR compared with a lower level. In contrast, Cotler et al [17] reported that there was no significant difference in basal IL-6 levels between the groups of responders and nonresponders to IFN therapy.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These findings were in agreement with the results of Nattermann et al [10], who reported that a higher level of IL-6 is significantly associated with SVR compared with a lower level. In contrast, Cotler et al [17] reported that there was no significant difference in basal IL-6 levels between the groups of responders and nonresponders to IFN therapy.…”
Section: Discussionsupporting
confidence: 94%
“…Thus, individuals can be classified into high (genotypes IL-6-174 GG and IL-6 -174 GC) and low (genotype IL-6-174 CC) IL-6 producers [9]. This polymorphism has been associated with response to HCV-specific treatment [10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the effect of IL6 C174G gene polymorphisms on the treatment of acute and chronic hepatitis C in human immunodeficiency virus (HIV)-infected patients has been reported previously (Nattermann et al, 2007), confirming our results. IL6, a major proinflammatory cytokine, is produced in various tissues, including activated leukocytes, adipocytes, and endothelial cells (Pradhan et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…Also this finding were in agreement with the results of Faisal et al [17] and Nattermann et al [18] who reported that a higher level of IL-6 is significantly associated with SVR compared with a lower level. In contrast, Cotler et al [19] reported that there was no significant difference in basal IL-6 levels between the groups of responders and non-responders to IFN therapy.…”
supporting
confidence: 93%